Time horizons and electricity futures: An application of Nicholas Georgescu-Roegen's general theory of economic production (2008)
This paper reports theoretical economic production work and uses electricity futures trading to illustrate its argument. The focus is relationships between time, production and tradition both in Nicholas Georgescu-Roegen's analytical representation of the production process (i.e., flow/fund model) and in his dialectical scheme dealing with the evolutionary changes in the economic process. Our main arguments are (1) the flow/fund model is designed to be employed in conjunction with attention to how the boundaries of a given process are determined and (2) process boundaries are dialectical distinctions—between process and not-process—that are strongly related to time and tradition. We propose that Georgescu-Roegen's The Entropy Law and the Economic Process is best understood as the elaboration of a general theory of economic production and we developed two conceptual tools (time and meta-funds), both of which are related to the dialectical distinction between process and not-process, which we use to operationalise this general theory. Finally, we demonstrate that, although trading in electricity futures is surprising if one uses a stock/flow vs services distinction (because electricity supply is classed as a service) it appears perfectly logical under Georgescu-Roegen's general theory: shortening time horizons, combined with a shift in the relationship between raw fuel supplies and power production procedures, lead to a shift in the status of electricity supply, from fund to flow.